The Challenges of Using ICT in the Teaching and Learning Process in Mozambique - Isabel, Isabel Augusto (Advances in Social Sciences Research Journal, 2024)
The Challenges of the Use of ICTs in the Teaching and Learning Process in Mozambique – is the subject of this study and arises in the context of the centrality that is attributed today to ICT as mediators of the teaching and learning process. The objective of this essay is to reflect on the challenges of using ICT in the teaching and learning process in Mozambique and to propose practices that guarantee the coherent use of digital resources, available at school and in the family, for pedagogical purposes. Methodologically, the study is based on a review of the existing literature on the subject. The pertinence of this study resides in the need to help teachers face the challenges imposed by the use of ICT in their work. The results reveal that educational practices demand from man an ability to adapt to changes in society. ICT have become indispensable in everyday school life in the 21st century alongside traditional methods. Therefore, it is necessary to equip educational institutions with technological equipment, as well as to make the teacher a critical, reflective and competent professional in the field of new technologies in order to help students to make the correct and intelligent use of ICT, allowing greater motivation for learning. Furthermore, each context must adapt the use of ICT according to its needs and particularities.